Sounding the Tricolore: France and the United States during World War ii - Fauser, Annegret (Les Cahiers de la Société québécoise de recherche en musique, 2015)
During World War ii, French music found itself in a unique position in the United States. As the sonic embodiment of an Allied nation, it was nonetheless subjected to musical identity politics that drew on stereotypes of France as an elegant, cosmopolitan, and even effeminate culture whose products needed the transformation of US reception to toughen themselves up for the global war, fought both on the battlefield and through propaganda. I focus on three aspects of this complex story of cultural mediation: the reception and adaptation of Claude Debussy’s music, especially Pelléas et Mélisande; American cultural artifacts representing France, such as the 1943 motion picture Casablanca; and the role of French composers and performers in the United States during the war.